Towards Sustainable Transportation Infrastructure - Haryati Yaacob; Nordiana Mashros; Sitti Asmah Hassan; Muhammad Naqiuddin Mohd Warid (Penerbit UTHM, 2024)
As the world’s population continues to grow, urbanization expands, and transportation needs evolve, the demand for sustainable and efficient transportation infrastructure becomes more critical than ever. The interaction between traffic management and pavement sustainability plays a vital role in shaping the future of our cities. This book provides a comprehensive overview of traffic dynamics and pavement innovations focusing on sustainability. The chapters in this volume are a collaborative effort from experts and researchers in transportation engineering, pavement materials, and urban planning. Throughout the chapters, readers will encounter various case studies and research findings that involve diverse facets of sustainable pavement practices and traffic engineering. Each chapter covers a specific topic, offering a blend of theoretical frameworks, laboratory works, and practical insights. The structure of this volume has been designed with the initial sections focusing on sustainable pavement solutions with detailed research on alternative pavement materials and asphalt modification techniques. From novel approaches to material selection to integrating recycling and green technologies, these chapters provide a comprehensive overview of the evolving landscape of sustainable pavement design. Subsequent sections focus on the fundamental principles of traffic engineering, covering topics such as traffic flow analysis, accident analysis, and traffic modelling. Ultimately, this book seeks to benefit a diverse audience, including practitioners, policymakers, researchers and students. We hope that the insights and knowledge shared within these chapters will serve as a source of inspiration in creating sustainable transportation infrastructure that harmonizes mobility, durability, and environmental responsibility.